ANALISIS BIAYA OPERASIONAL KENDARAAN ANGKUTAN UMUM ANTAR KABUPATEN ( MAUMERE- MBAY ) - Dominikus laru (SIARTEK - Jurnal Teknik Sipil dan Arsitektur, 2024)
Public transportation is crucial for mobility on the island of Flores, East Nusa Tenggara, especially in areas with limited accessibility. The Maumere-Mbay route, which connects Sikka Regency with Nagekeo Regency, is essential for passenger and freight transportation, contributing significantly to the local economy. The Sinar Rembulan Bus provides public transportation services in both urban and rural areas. This research, conducted by the Department of Public Works, aims to identify the factors influencing vehicle operational costs.The research results revealed that the actual fare for the Sinar Rembulan Maumere-Mbay Bus was IDR 100,000 per person. According to the Department of Public Works, the vehicle operating costs for the Sinar Rembulan bus and Maumere-Mbay fare should be IDR 104,727 per person. In contrast, as per the operational costs outlined in the Transportation Service's Governor's regulation number 101 of 2019 for Fast Nusa Tenggara, the vehicle operational costs for Maumere-Mbay are IDR 81,661 per person. The cost difference between the author's calculated fare and the operational costs from the Transportation Service is IDR 23,066 per person, while the disparity between the author's calculations and the actual costs is IDR 4,727 per person.